Development of copper based anti-inflammatory drugs: histodine derivatives - Mohajane, Mamohale (Department of Chemistry, 2014)
Methyliminodiacetylhistidine dimethyl ester could not be synthesised. However the other two ligands, glycine and glycyl-L-histidine were purchased and used for this study. The equilibrium constants of the ligand (glycyl-L-histidine) and the ligand complexes with Cu(II), Ni(II) and Zn(II) were investigated with glass electrode potentiometry and isothermal titration calorimetry at 25Â±0.01oC at an ionic strength 0.15M with NaCl. Potentiometric studies show that glycyl-L-histidine has three dissociable protons, and the neutral form of the ligand forms around pH 6.60. Potentiometric results of copper(II) complexes with glycyl-L-histidine were compared to the potentiometric titration of the ligand with Ni(II) and Zn(II). Copper(II) complexes of glycyl-L-histidine were more stable than Ni(II) and Zn(II) complexes of glycyl-L-histidine. The potentiometric results for these systems were in good agreement with the literature results. From the potentiometric studies, the LH form of glycine was more stable than the LH form of glycyl-L-histidine by 1.19 log units. The second protonation of glycyl-Lhistidine is on the imidazole ring and hence there is so comparable protonation site for glycine. Instead the third protonation step of glycyl-L-histidine is comparable to the second protonation step of glycine. The ML form of Cu(II)-glycyl-L-histidine complexes was more stable than that of Cu(II)-glycine complexes by 1.07 log units. ML was the only common species for the two systems. The interaction between copper(II) and glycyl-L-histidine was also studied with isothermal titration calorimetry (ITC) from pH 5 to pH 8. This was compared to a simpler system of glycine. The change in speciation for this method was characterized by the N value. The speciation from ITC results followed that of potentiometric results. The ML species of Cu(II) and glycine formed in acidic solutions, and the ML2 formed in basic solutions. In this pH range, the ML species of Cu(II) and glycyl-L-histidine were the most predominant species in solution. The ITC results agreed with the potentiometric results. At pH 5 where ML was the most predominate species in both the Cu(II)-glycine system and the Cu(II)-glycyl-L-histidine v system (N 1) Log K of the glycyl-L-histidine system was greater than that of the glycine system. The structures of the complexes were predicted with ultraviolet-visible (UV-Vis) spectrophotometry. The visible spectra obtained for the different Cu(II)/Glycyl-Lhistidine species in solution were typical of Cu(II) complexes in a tetragonally distorted, octahedral environment. The molar extinction coefficients are also typical of Cu(II) complexes and reflect the distortion of the metal-ion environment. The sequence of protonation/deprotonation of the ligand was studied with 1H NMR spectroscopy. The first deprotonation of glycyl-L-histidine occurred at very acidic environments, and this was the deprotonation of the carboxylate proton. The second deprotonation occurred at one of the imidazole nitrogens and the last one occurred in highly basic environments. This was the deprotonation of the NH2 terminal. The structure of complexes of Cu(II) with glycyl-L-histidine were also studied by 1H NMR. Form 1H NMR results, the active binding sites for glycyl-L-histidine are the imidazole nitrogens, the amide nitrogen and the terminal NH2 group. The imidazole nitrogen involved in coordination first, followed by the amide nitrogen, followed by the terminal NH2 group The capacity with which the ligand can increase the low molecular weight Cu(II) complexes in blood plasma was studied using a computer model of blood plasma. At reasonable concentrations, the ligand was not able to mobilise endogenous copper. Most of the ligand existed as LH and LH2 in blood plasma. Moreover, glycyl-Lhistidine increased the low molecular weight complexes of Zn(II) more than of Cu(II).